If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = x + -1(-14) Multiply -1 * -14 13 = x + 14 Reorder the terms: 13 = 14 + x Solving 13 = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 13 + -1x = 14 + x + -1x Combine like terms: x + -1x = 0 13 + -1x = 14 + 0 13 + -1x = 14 Add '-13' to each side of the equation. 13 + -13 + -1x = 14 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 14 + -13 -1x = 14 + -13 Combine like terms: 14 + -13 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 6h+h=30 | | 4x+34=114 | | 21a^5-7a^6= | | p+0.06=360.40 | | w-7/2w-14 | | f(x)=2.3x+7 | | -8=-4+v | | 16a^4-8a^6= | | -4x+3=6x-63 | | 4/9x^2-16=0 | | 3(0.3m+6)+m=75 | | 13=-7b-6b | | x^7-x^5= | | -x=-a/13 | | (1/2)(5x)(4x-1)= | | -n+7n=18 | | x^2+29x+79=0 | | 9x-29/10 | | 4(m-s)=24 | | 2(4z-5-3)=166-48 | | x+41=-90 | | 2/3x5/1 | | Y-4=-1/4(x-3) | | x+41= | | (-6)+(6)= | | 8x=-120/18 | | 40+3a=-5 | | 3(3x-6)=-(x-2) | | -2/3u=-4 | | (X-8)(3x+10)=0 | | 7w+54=61 | | 12x-3x^2+42= |